Faktor-Faktor yang Mempengaruhi Kualitas Dokumentasi Keperawatan: A Systematic Review - Sholihin Sholihin; Tintin Sukartini; Aria Aulia Nastiti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Nursing documentation is the most important part of the nursing profession, providing structured, consistent and effective communication to give quality services to patients based on professional and legal standards. Objective: To identify scientific evidence about the factors that influence the quality of nursing documentation. Methods: This systematic review was compiled based on study of literature from various journal data bases in the last 5 years, including Scopus, Sciencedirect, Proquest, and Google Scolar by conducting a comprehensive review using the PRISMA guidelines. Keywords used were "nursing documentation" OR "Standard Nursing Language" OR "quality of nursing documentation" AND "Quality Diagnosis Intervention Outcome". The articles used to compile this systematic review were 13 original articles on data base identification. Results : the factors affecting the quality of documentation were the level of knowledge, abilities, facilities, patient and nurse ratios, workplace climate, leadership and organizational models, training in nursing process standards, nursing language standards and accreditation. Conclusion: The quality of documentation increased when the affecting factors were improved. Suggestion: This systematic review can be used as a guideline in implementing nursing documentation in hospitals with the aim of producing quality nursing documentation. Keywords: nursing documentation; quality ABSTRAK Latar Belakang: Dokumentasi keperawatan merupakan bagian terpenting pada profesi keperawatan, menyediakan komunikasi secara terstruktur, konsisten dan efektif untuk memberikan pelayanan yang berkualitas pada pasien berdasarkan standar profesional dan legal. Tujuan: Untuk mengidentifikasi bukti ilmiah tentang faktor-faktor yang mempengaruhi kualitas dokumentasi keperawatan. Metode: Systematic review ini disusun berdasarkan studi literatur dari berbagai data base jurnal pada 5 tahun terakhir, meliputi Scopus, Science Direct, Proquest, dan Google scholar dengan melakukan review secara komprehensif menggunakan pedoman PRISMA. Kata kunci yang digunakan "nursing documentation" OR "Standard Nursing Language" OR "quality of nursing documentation" AND "Quality Diagnosis Intervention Outcome". Artikel yang digunakan untuk menyusun systematic review ini berjumlah 13 artikel original pada. Hasil: Faktor-faktor yang mempengaruhi kualitas dokumentasi adalah tingkat pengetahuan, kemampuan, fasilitas, rasio pasien dan perawat, iklim tempat kerja, model kepemimpinan dan organisasi, pelatihan standar proses keperawatan, standar bahasa keperawatan dan akreditasi. Kesimpulan: Kualitas dokumentasi meningkat apabila faktor-faktor yang mempengaruhi tersebut ditingkatkan dan diperbaiki. Saran: Systematic review ini dapat digunakan sebagai pedoman dalam pelaksanaan dokumentasi keperawatan di Rumah Sakit dengan tujuan menghasilkan dokumentasi keperawatan yang berkualitas. Kata kunci: dokumentasi keperawatan; kualitas